PENDAPAT MASYARAKAT TERHADAP SERTIFIKASI HALAL MAJELIS ULAMA INDONESIA (MUI) TENTANG PEMOTONGAN AYAM POTONG - Hidayani (Program Studi Perbankan Syariah, 2020)
The effect or slaughtering relation in syar???ih way (halal) on broiler product with buying interest at Inpres Kamboja. The purpose of this research in theoretical hopefully there will be a knowledge progres for economic Islam theory especially about how important slaughter in syar???ih way (halal) for the product that will be comsumed by muslim. In this research, the writer is about to position to make it even stronger about the theory which has existed before. Islam consumption theory and communication theory. In an effort to answer the problem of this research, the writer is using quantitative research. Therefore, the existence of halal sertification on broiler product means the entrepreneur has been contribute in applying the principles of Islamic comsumption for consumers in Indonesia. Next, about public awareness of the broiler product because of halal sertification or syari???ah slaughtering can provide employment and health insurance in society. So that in the end it will reduce the development of illegal broiler houses and provide new employment or reducing unemployment because it absorbs labor as more consumer demand on broiler in syari???ah way.